Exit Site Care in Peritoneal Dialysis: Silver as a Possible Strategy? - Giuseppe, Paribello; Fortuna, Papa; Chiara, Ganzerli Maria; Chiara, Del Prete; Ivana, Capuano; Daniela, Pacella; Giuseppina, Sannino; Gianluca, Rompianesi; Antonio, Pisani; Eleonora, Riccio (Journal of Clinical Nephrology, 2024)
Peritoneal dialysis (PD) is a well-tolerated home renal replacement therapy for patients with end-stage renal disease. One of the critical points for the success of a PD program is the care of the peritoneal catheter and the exit site. A target for the incidence of infections/year should not exceed 0,40. The aim of the study was to observe whether our exit-site cleansing and dressing method, which involves the application of silver-releasing dressing may be associated with a reduction in the incidence of exit-site infections compared to the data reported in the literature. The data of 51 patients attending the Peritoneal Dialysis DH of the AOU Federico II in Naples in the period between July 2021 and September 2023 were analyzed. Overall, 27670 catheter days were analyzed with an average incidence of 0.23 infections/year/patient. The average incidence (0.23) is lower than the target suggested by the ISPD (0.4 infections/year/patient) and the average estimated in the USA (0.5-0.6 infections/year/patient). The average incidence from 2021 to 2023, equal to 0.23 episodes/year/patient, is therefore lower than the incidence of 2014-2015 (0.38 episodes/year/patient), a two-year period in which we did not use dressings with silver Exit-Pad. The use of Exit-Pad silver ion-releasing dressings Ag may further hinder the development of such infections by reducing the failure of peritoneal treatment and the transition to hemodialysis.